Cooperative enhancement of deoxyribozyme activity by chemical modification and added cationic copolymer. Issue 1 (1st December 2016) - Saito, Ken; Shimada, Naohiko; Maruyama, Atushi
Abstract: Deoxyribozymes (DNAzymes) having RNA-cleaving activity have widely been explored as tools for therapeutic and diagnostic purposes. Both the chemical cleaving step and the turnover step should be improved for enhancing overall activity of DNAzymes. We have shown that cationic copolymer enhanced DNAzyme activity by increasing turnover efficacy. In this paper, effectｓ of the copolymer on DNAzymes modified with locked nucleic acids (LNA) or 2′- O -methylated (2′-OMe) nucleic acids were studied. The copolymer increased activity of these chemically modified DNAzymes. More than 30-fold enhancement in multiple-turnover catalytic activity was observed with 2′-OMe-modified DNAzyme in the presence of the copolymer. DNAzyme catalytic activity was successfully enhanced by cooperation of the added copolymer and chemical modification of DNAzyme. Abstract :